PERTIMBANGAN TINGKAT MATERIALITAS, RISIKO DAN STRATEGI DALAM AUDIT: FAKTOR YANG MEMPENGARUHINYA - Anisa Ismelya Putri; Elyanti Rosmanidar; Abdul Matin Aji Saka; Bunga Jelita; Daffa Novita Sari; Rifki Firmansyah; M Ulil Amri (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
The audit process is crucial to ensure the fairness of financial statements, where auditors must assess the level of materiality, audit risk, and appropriate audit strategies. Materiality guides auditors in identifying misstatements that could affect users' decisions, while audit risk refers to the possibility of issuing an inaccurate opinion on financial statements that contain significant misstatements. These elements are interconnected and form the basis for the auditor's decision-making. Factors such as professional ethics, auditor professionalism, experience, and external pressures significantly influence the consideration of materiality and risk. In addition, the audit strategy encompasses the overall planning, timing, and scope of testing, which are influenced by the complexity of the entity and the effectiveness of internal controls. Studies reveal that high audit risk drives auditors to be more cautious in setting materiality thresholds and leads to more extensive testing. Individual auditor factors, such as ethics and experience, further shape their decision-making process. In conclusion, a comprehensive understanding of materiality, risk, and audit strategy is crucial for conducting an effective audit. Continuous training in this field is recommended to enhance auditor competence and maintain audit quality, in addition to strengthening the internal control system to facilitate an efficient audit process.